Persepsi Karyawan Terhadap Manajemen Konflik dan Dampaknya Pada Kinerja Organisasi - Nor Hendra Safutra Bin Nuratim; Lathifatur Robbaniyyah; Dini Putri Hidayah; Mu’alimin Mu’alimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the influence of conflict management on employee performance in organizations. Conflict that is not managed properly can have a negative impact on productivity, but if handled constructively, conflict can be a source of innovation and performance improvement. Effective conflict management includes strategies such as avoiding, accommodating, compromising, competing, and collaborating. Proper conflict management can increase collaboration, trust, and creativity in the workplace. This study also highlights the importance of emotional intelligence in managing conflict, where emotionally intelligent individuals are better able to resolve disputes constructively, thus positively impacting team performance.